2019
DOI: 10.1080/02670844.2018.1560912
|View full text |Cite
|
Sign up to set email alerts
|

On structure and oxidation behaviour of non-stoichiometric amorphous aluminium phosphate coating

Abstract: The purpose of this study was to investigate the structure and oxidation behaviour of nonstoichiometric aluminium phosphate coating. Phase composition analysis was performed by X-ray diffractometer (XRD). Fourier transform infrared (FTIR) was used for molecular spectroscopy. The micro-structural studies were investigated by TEM. AISI 304 stainless steel substrates were dip coated in the aluminium phosphate solution to evaluate the cyclic oxidation behaviour. The oxidised samples were characterised by SEM/EDS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…As an example, the composite formed from phosphorylated polyvinyl alcohol (PPVA) was found to contain better flame-retarding and anti-corrosion properties because of the generation of a second 3D network by the newly incorporated phosphate groups following the inter-and intra-molecular hydrogen bonding [1]. Moreover, other similar studies on PPVA composites (PPVA-graphene aerogel, PPVA-polyaniline) found significant aqueous and thermal stabilities, in addition to the mechanical resistance due to the newly involved self-assembling feature [2,3]. However, other distinctively direct phosphate coatings were also investigated to enhance the internal properties, e.g., aluminum phosphate (AlPO 4 ), a type of naturally occurring compound with its low density, high melting point, and hardness when used in non-stoichiometric amounts, offers superior oxidation resistances and thermal degradations (over 1000 • C) [2].…”
Section: Introductionmentioning
confidence: 94%
“…As an example, the composite formed from phosphorylated polyvinyl alcohol (PPVA) was found to contain better flame-retarding and anti-corrosion properties because of the generation of a second 3D network by the newly incorporated phosphate groups following the inter-and intra-molecular hydrogen bonding [1]. Moreover, other similar studies on PPVA composites (PPVA-graphene aerogel, PPVA-polyaniline) found significant aqueous and thermal stabilities, in addition to the mechanical resistance due to the newly involved self-assembling feature [2,3]. However, other distinctively direct phosphate coatings were also investigated to enhance the internal properties, e.g., aluminum phosphate (AlPO 4 ), a type of naturally occurring compound with its low density, high melting point, and hardness when used in non-stoichiometric amounts, offers superior oxidation resistances and thermal degradations (over 1000 • C) [2].…”
Section: Introductionmentioning
confidence: 94%
“…6,7 However, the hexavalent chromium (Cr [VI]) in waste water produced during the surface treatment of aluminum is highly toxic and carcinogenic. 8 Thus, a variety of chromate-free and environmentally friendly conversion coatings have been developed, such as phosphate/permanganate conversion coating, 9 molybdate conversion coating, 10 silicate conversion coating, 6 zirconium/titanium conversion coating, [11][12][13] and cerium (Ce) conversion coating. [14][15][16][17][18] Among these coatings, Ce conversion coating is a promising alternative to Cr (VI) conversion coating due to its unique properties such as environmental friendliness, high adhesive strength to the substrate, and excellent corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the inorganic binders without the VOC are completely environmentally friendly and have become a hot spot for coating research. They mainly include phosphate [18,19], silica sol [20,21] and silicate coatings [22,23]. Silica sol paints form a film by polymerization of silanol group but cohesion is larger during polycondensation, which is likely to cause the coatings to crack or even cause large-areas to fall off.…”
Section: Introductionmentioning
confidence: 99%